The Efficacy of Intravenous Analgesia and Various Nerve Blocks for Pain Management in Elderly Patients With Hip Fractures: A Meta‐Analysis - Yuping Liu; Li Zhou; Xin Wang (Orthopaedic Surgery, 2025)
ABSTRACT Pain management in elderly patients with hip fractures has received more and more attention, which is crucial for promoting recovery and reducing complications. At present, there are various and controversial analgesic methods for this population. This meta‐analysis evaluated the analgesic effects and side effects of intravenous analgesia compared to different nerve block techniques, including femoral nerve block, fascia iliaca block or pericapsular nerve group block, in this patient group. The study was conducted following the PRISMA 2020 guidelines. A search was performed in October 2024 across PubMed, Web of Science, Cochrane Library, and Embase. Pain scores at different time points, supplemental analgesic morphine consumption, and adverse reactions were compared between intravenous analgesia and nerve blocks. Data were collected from 12 studies and 1157 elderly patients using intravenous analgesia and nerve block after hip fracture, with no differences in sample size, mean age, or percentage of females between the two groups at baseline. Compared to intravenous analgesia, nerve blocks showed significant advantages in the pain score of 2 h after block (SMD‐0.80; 95% CI: −1.23 to −0.38; I2 = 90%) and the supplemental analgesic morphine consumption (SMD = −0.46; 95% CI: −0.73 to −0.19; I2 = 59%). The incidence of adverse reactions and the pain scores at various time points also demonstrated significant differences between the two groups. The application of nerve blocks in elderly patients with hip fractures demonstrates significant clinical advantages, particularly in postoperative pain management, decreasing opioid use, and reducing postoperative complications.